PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN DASAR-DASAR PROGRAM KEAHLIAN KELAS X DKV - Rahmatin Anisa; Heri Mulyono; Mourend Devegi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The primary objective of this study is to develop interactive learning media for the subject of Basic Expertise in Class X DKV, utilizing the Adobe Animate application. This approach aims to ensure the validity and practicality of its implementation. The research methodology employed is Research and Development (R&D), which follows the ADDIE model encompassing five essential phases: analysis, design, development, implementation, and evaluation.The validation results provided by media experts indicate a percentage of 86.57%, falling within the category of